Causal association between antidiabetic drugs and erectile dysfunction: evidence from Mendelian randomization - Feng, Lin; Jinhua, Wu; Shulin, Guo; Jiangping, Xie; Zhongxiang, Liao; Xiaohong, Liao (Frontiers in Endocrinology, 2024)
Antidiabetic drugs are widely used in clinical practice as essential drugs for the treatment of diabetes.The effect of hypoglycemic drugs on erectile dysfunction has not been fully proven due to the presence of multiple confounding factors.Two-sample Mendelian randomization (TSMR) was used to examine the causal effect of antidiabetic drugs (including metformin, insulin and gliclazide) on erectile dysfunction. We used five robust analytic methods, of which the inverse variance weighting (IVW) method was the primary method, and also assessed factors such as sensitivity, pleiotropy, and heterogeneity. Effect statistics for exposures and outcomes were downloaded from publicly available data sets, including open Genome-Wide Association Studies (GWAS) and the UK Biobank (UKB).In some of the hypoglycemic drug use, there was a significant causal relationship between metformin use and erectile dysfunction [Beta: 4.9386; OR:1.396E+02 (95% CI:9.13-2135); p-value: 0.0004), suggesting that metformin increased the risk of erectile dysfunction development. Also, we saw that gliclazide use also increased the risk of erectile dysfunction [